'It is not good for the person to be alone'1: The capabilities approach and the right to communicate. (December 2022) - Schejter, Amit M
For decades, attempts have been made to define a 'right to communicate'. The rise of media technologies, which are characterized by abundance of channels and information, interactivity, mobility, and multimediated messaging, has allowed to rethink this right in a context converging traditional media and telecommunications and referring to communicating as an essential human capability. Applying Amartya Sen's capabilities approach to communications, we argue that communicating is a capability required to realize such functionings as participating in political, cultural, social, educational, and commercial life and is essential to promote belonging to a collective. The 'negative' right to free speech should be replaced by a positive right to communicate, which should include free speech, access to information, privacy, and utilization of communications in order to belong to a community.